Indonesian language learning based on ecological intelligence: A case of Bengawan Solo Nature School - Saputra, Aldi Dwi; Ginting, Dasa Oktaviani Br; Pramadhanti, Dhelinta Fitri; Muftihah, Nani; Saddhono, Kundharu (Research Journal in Advanced Humanities, 2023)
Ecological intelligence has a complex structure for improving education. Learning Indonesian needs to contain ecological intelligence. It aims to make students love, protect and preserve the environment. The purpose of this article is to analyze the way teachers carry out ecological intelligence mapping and assess the potential of advanced students at the Bengawan Solo Natural School. This research method is qualitative with a case study approach. Data and data sources were obtained from the results of document analysis, observation, and in-depth interviews with teachers and students. Test the validity of the data used in this study is the technique of data triangulation and source triangulation. The results of this study are that the teacher maps ecological intelligence by becoming a partner or co-parent in developing the potential that exists in students based on spiritual, intelligence, social-emotional, and physical and motor skills of students. The Bengawan Solo natural school has four types of assessment to measure the potential of students. The types of assessments are (1) moral assessments in the form of Al-Qur'an report cards; (2) leadership assessment in the form of narrative report cards; (3) cognitive and scientific assessments in the form of numerical report cards and portfolio reports; and (4) business assessment in the form of business reports. The Bengawan Solo Nature School does not only educate students to become great people in the future, but also has the character of loving nature and being useful to others.